Influence of adipose tissue immune dysfunction on childhood obesity. (June 2022) - Dai, Wanlin; Liu, Xiyan; Su, Han; Li, Xuan; Xu, Yingxi; Yu, Yang
Abstract: In recent decades, a dramatic rise has been observed in the prevalence of obesity in childhood and adolescence, along with an increase in fetal microsomia rates. The increased risk of obesity during this key period in development negatively affects the health of the individual later in life. Immune cells residing and recruited to white adipose tissue have been highlighted as important factors contributing to the pathogenesis of childhood obesity. Immune dysfunction in the context of obesity begins early in childhood, which is different from the pathological characteristics and influencing factors of adipose immunity in adults. Here, we explore the current understanding of the roles of childhood and early life events that result in high risks for obesity by influencing adipose tissue immune dysfunction under the pathological condition of obesity. Such knowledge will help in determining the mechanisms of childhood and early life obesity in efforts to ameliorate chronic inflammation-related metabolic diseases. Graphical Abstract: Overview of influence of adipose tissue immune dysfunction on childhood obesity. Obesity in childhood and early life lies in both genetic predisposition and obesogenic nurturing environment. Initially, unhealthy lifestyles, such as poor dietary patterns, insufficient exercise, and inadequate sleep, are proved to be negative factors for obesity prevention from an early age. Next in importance, the variety of obesity-related genomic alterations is extensive and is still being studied. What's more, there are particularly obvious correlations between adiposity at birth or infancy and the progression of obesity or metabolic diseases across the whole life stages. Maternal obesity, exposure to endocrine disruptors during pregnancy, and insufficient breastfeeding possibly result in dysfunctional adipose tissue and defective immune function during the very early stages of life, and even lasting until adulthood. Finally, dysregulation of gut microbiota is regarded as an early trigger to the development of obesity and related systemic low-grade inflammation. Interactions between gut microbiota alterations and lipid dysmetabolism plays an important role in individual subsequent adipose tissue development and exerting immune or endocrine function. ga1 Highlights: Adipose immune function is defined in early stage of life, and its disorder will lead to a series of chronic diseases in adulthood. Cytokines derived by obese adipose immune cells aggravate insulin resistance and the whitening of brown and beige adipocytes. Unhealthy lifestyles play key roles in childhood obesity by affecting adipose immunity.